Gambaran Kristal Hemoglobin pada Bercak Darah yang Terpapar Beberapa Sabun Krim Menggunakan Tes Teichmann dan Takayama - Pangaribuan, Welly N; Asni, Enikarmila; Indrayana, Mohammad Tegar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe biologic sample like bloodstains are precious physical evidence thatcan be found at any crime scene. Bloodstains that be found can indicate struggleor murderer case and identification of bloodstains found at criminal scene cangive information about actual criminal acts. The criminals often try to remove orcamouflage bloodstains by using cleaning agents like cream detergent that makesbloodstains contamined with detergent surfactant and may be affect the chemicalbloodstains identification using Teichmann and Takayama test. The purposes ofthis experiment are to know the description of hemoglobin crystal at contaminedbloodstain with some cream detergents using Teichmann and Takayama test. Thisexperiment is the experimental description. This experiment has done inBiochemical Laboratory Medical Faculty of Riau University. There’re 38 slidesthat made in this experiment with twice experiment (duplo). The bloodstain slideswere washed using cream detergent A, B, C, D, E, and F once until three times.The result of this experiment was positive in all bloodstain slide that washed bycream detergent when it tested with Teichmann and Takayama test.Keywords: bloodstain, hemoglobin crystal, cream detergent, Teichmann andTakayama.